A Fractal Approach to Microstructural Changes during the Storage of Yoghurts Prepared with Starter Cultures Producing Exopolysaccharides. Issue 2 (13th November 2013) - Smoczyński, Michał; Baranowska, Maria
Abstract Changes were evaluated in the properties of the microstructure during storage of yoghurts obtained with three commercial bacterial starter cultures differing in their ability to produce exopolysaccharides (EPS). The syneresis and rheological parameters were investigated during 28 days of storage. Changes in yoghurt microstructure were also monitored by image analysis processing to calculate the fractal dimension. Yoghurts prepared with EPS‐producing lactic acid bacteria showed higher values of viscosity and hysteresis loop area and lower amounts of whey separation. The calculated fractal dimension indicated changes in the porosity of yoghurt gels during storage. Different relationships between fractal dimension and syneresis and hysteresis loop area were observed for EPS and non‐EPS yoghurts, which may suggest alternative mechanisms of their microstructural behavior and confirm the important role of EPS for yoghurt properties. Fractal geometry provides a powerful method to investigate the properties of irregular structures which are otherwise undetectable. Practical Applications Yoghurt has a porous structure built of a protein network. Many physical properties of yoghurt depend on this microstructure. EPS produced by various lactic acid bacteria affect yoghurt microstructure and texture properties to a large extent. During microscopic observation, characterization of such objects is often limited to verbal description and many subtle differences between similar structures escape detection. In this case, fractal geometry can be used for precise mathematical description of such microstructure. The presented method of image analysis and calculation of the fractal dimension of pores in yoghurt microstructure can be a useful tool for yoghurt comparison and even classification of lactic acid bacteria properties.